Increased serum EGF but not SDF-1 levels are associated with the pathophysiology and development of generalized anxiety disorder - A. S. M. Roknuzzaman; MMA Shalahuddin Qusar; Mohammad Shahriar; Sardar Mohammad Ashraful Islam; Md. Rabiul Islam (Scientific Reports)
Abstract Generalized anxiety disorder (GAD) is a common and persistent mental illness accompanied by uncontrollable worries for daily staff. Physiological, environmental, genetic, and daily stress from surroundings is involved in developing GAD. Here, we aimed to assess the association of stromal cell-derived factor-1 (SDF-1) and epidermal growth factor (EGF) in the pathophysiology of GAD and their role as diagnostic tools. This case-control study recruited 50 GAD patients from the psychiatry department of a tertiary care teaching hospital in Dhaka city and 38 age-sex-matched healthy controls (HCs) from the surrounding areas. A qualified psychiatrist conducted standardized psychiatric interview to diagnose GAD patients and evaluate HCs by applying the diagnostic and statistical manual for mental disorders, 5th edition (DSM-5) and used the GAD-7 scale to assess the severity of the GAD symptoms. After confirming the inclusion and exclusion criteria, we collected 5 ml blood samples from each participant. We measured serum SDF-1 and EGF levels using ELISA techniques. We observed increased serum levels of EGF in GAD patients compared to HCs (5.91 ± 3.90 ng/ml vs. 1.59 ± 1.08 ng/ml; p < 0.001). Also, this increment is positively associated with the severity of GAD in patients (r = 0.479, p = 0.002). The receiver operating characteristic analysis showed good diagnostic performance (AUC 0.869, p < 0.001) with high sensitivity (82.5%), and specificity (81.1%) at cut off value of 2.31 ng/ml. However, we didn’t find significant differences in serum SDF-1 levels between GAD patients and HCs (11.96 ± 4.50 ng/ml vs. 12.70 ± 11.76 ng/ml; p = 0.337). The present study suggests that GAD patients have increased serum EGF levels but not SDF-1 levels compared to HCs and that increased EGF levels are associated with increased GAD symptoms as well. Moreover, EGF levels could serve as a biomarker for GAD However, further interventional studies with larger and homogeneous samples are suggested to confirm and establish these findings.